Electronic medical records (EMR) implementation readiness using the DOQ-IT framework (Nursing and Health Sciences Journal (NHSJ), 2025)
The digital transformation of Indonesia's healthcare sector requires health facilities to be ready to effectively implement Electronic Medical Records (EMR) in compliance with national regulations. This study aimed to analyze the readiness level of EMR implementation using the DOQ-IT framework, comprising human resources, organizational culture, leadership, governance, and technological infrastructure. A qualitative descriptive method was employed through questionnaires and in-depth interviews, utilizing a snowball sampling technique with 25 respondents and six key informants, and validated by four experts (three internal and one external). The findings indicate that the clinic falls within Range II (Moderately Ready); computers are available in the registration, pharmacy, and laboratory units, but the system is not yet fully integrated. Following external validation, the clinic successfully integrated patient visit data with the national SATUSEHAT platform, in accordance with the Ministry of Health's guidelines. The study concludes that the clinic's digital readiness is progressing positively toward complete transformation. However, further improvement is required in staff training, network enhancement, and the development of Standard Operating Procedures for digital data quality assurance.